Light Pollution Phenomenon: Prior Knowledge, Attitudes, and Awareness of Physics Undergraduate Students at State University of Surabaya - Della Shinta Bestiantono; Eko Hariyono; Nadi Suprapto (Jurnal Penelitian Pendidikan IPA, 2023)
This is preliminary research by undergraduate students in Physics Department, at Surabaya State University. This study aims to examine the prior knowledge, attitudes, and awareness of the light pollution phenomenon. The preliminary study was carried out on questionnaire sheets. The questionnaire sheets were given to 30 students of the 2020 class physics education program. The questionnaire consists of 21 item questions, divided into 16 Likert scale questions and 5 open questions. The development of the questionnaire considers indicators of prior knowledge, attitudes, and awareness in the case of the light pollution phenomenon. In this study, data analysis was carried out through quantitative analysis. The questionnaire as the research instrument was tested in two stages: validity and reliability using SPSS software statistics. The validity test using Pearson correlation got a 0.779 score. The reliability test using Cronbachâ€™s alpha got a 0.800 score. The result of the study showed that 76% of undergraduate students have an average initial knowledge about light pollution with the â€œgoodâ€ category, and 68% of them have an attitude of caring for the environment in the case of light pollution phenomena with the category of â€œcareâ€. And the final result is that 66% of them realize that the impact of light pollution is a crucial issue nowadays. Further research is needed for developing the learning media with reference to the current status of prospective physics teachers